2010
DOI: 10.1016/j.jsams.2009.10.304
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of weight gain in young women: A review of the literature

Abstract: Abstract:Background: Young adult women (18-36 years) are gaining weight at rates higher than women in other age groups. Given its long term deleterious health effects, it is important to know the determinants of this weight gain. However, other than in relation to pregnancy, little is known about the determinants of weight gain in this population group.Method: Papers examining non-pregnancy weight gain in young women were identified through a literature search in PubMed in August 2008. Subsequently, reference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
(45 reference statements)
1
7
0
Order By: Relevance
“…Interestingly, steady increases in the cognitive symptoms corresponded with an increasing BMI of approximately 1 kg/m 2 every 3 years from age of 11 (BMI mean = 19.41 [SD = 3.76]) to age of 25 (BMI mean = 25.68 [SD = 6.02]). Importantly, this increase corroborates the previous findings from the GUTS cohorts and data showing that women in young adulthood gain weight at higher rates than females in other age groups . This rise in BMI might be one reason why concerns about body weight/shape continue to increase into young adulthood, whereas other symptoms (e.g., binge eating and purging) that may be less directly predicted by increases in BMI remain stable.…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, steady increases in the cognitive symptoms corresponded with an increasing BMI of approximately 1 kg/m 2 every 3 years from age of 11 (BMI mean = 19.41 [SD = 3.76]) to age of 25 (BMI mean = 25.68 [SD = 6.02]). Importantly, this increase corroborates the previous findings from the GUTS cohorts and data showing that women in young adulthood gain weight at higher rates than females in other age groups . This rise in BMI might be one reason why concerns about body weight/shape continue to increase into young adulthood, whereas other symptoms (e.g., binge eating and purging) that may be less directly predicted by increases in BMI remain stable.…”
Section: Discussionsupporting
confidence: 88%
“…Similar trends have been reported in the USA (Flegal et al, 2010) and Europe (Berg et al, 2005;Howel, 2010). Young adulthood is a particularly vulnerable time for weight gain among women (Wane et al, 2010). The Australian Longitudinal Study on Women's Health (ALSWH) reported that from 1996 to 2006, women aged mostly in their 20 s gained an average of 0.6 kg per year, which was 30% greater than the weight gained by middle-aged women (Adamson et al, 2007).…”
Section: Introductionmentioning
confidence: 68%
“…Life transitions related to student status, employment, family structure and health status also were reported by women as critical periods that hindered weight management. Both young adulthood and mid‐life appear to be crucial intervals for weight gain (Ball et al ., ; Wane et al ., ), and life stress and significant life events also have been associated with weight gain (Elfhag & Rossner, ). Women perceived that their capacity for achieving and maintaining WL was lower than for men, consistent with evidence demonstrating that women are twice as likely as men to experience major weight gain over the life course (Williamson et al ., ).…”
Section: Discussionmentioning
confidence: 99%